Multifunctional Adsorbent with Antibacterial Properties Derived from Municipal Sludge for Synergistic Removal of Fluoride, Uranium, and Dyes - Weiwei Yang; Xiaoxuan Fan; Wenfeng Li; Gang Wei; Lei Guo (Applied Sciences)
With the continuous expansion of urban areas, the treatment of urban sewage is facing significant challenges. Tens of thousands of tons of municipal sludge (MS) are produced annually, which not only occupies substantial land resources but also poses potential environmental threats, thereby complicating wastewater treatment processes. Proper management of MS has thus become a critical issue requiring urgent attention. Meanwhile, water pollution continues to worsen, endangering both ecological systems and human health. MS contains a variety of organic compounds with active functional groups capable of forming strong coordination interactions with various waterborne pollutants. Building on this foundation, we successfully develop a multifunctional adsorbent using MS as the raw material through biomineralization. The synthesized adsorbent shows outstanding performance, exhibiting high adsorption capacity for fluoride (F−) and hexavalent uranium (U(VI)) in high-fluorine uranium-containing wastewater, effectively reducing the concentrations of these harmful substances. Additionally, the adsorbent shows strong affinity for the cationic dye methylene blue, making it highly suitable for the treatment of wastewater from the printing and dyeing industries. Notably, the adsorbent also possesses antibacterial properties, demonstrating significant bactericidal activity against Gram-negative E. coli in wastewater. The multifunctional adsorbent not only offers a novel solution to enhancing water quality and safety, but also represents a promising strategy for sustainable wastewater treatment.